Impact of Hiv on Family Life of Infected Women: Exploring the Impact of HIV/AIDS on Women's Lives in India (Journal of Advances and Scholarly Researches in Allied Education, 2014)
India has registered a significant rise in the HIV/AIDScases with nearly 2.4 million people estimated to fall prey to this deadlyviral infection. However, between 2001 and 2009, HIV incidence fell by nearly25 percent and the national prevalence was evaluated to be less than 1 percent.From the total number of HIV infected Indians, nearly 39 percent are women. HIVhas emerged as a diverse epidemic in India with strong presence in a few stateslike Andhra Pradesh, Maharashtra, Karnataka and Tamil Nadu, that make up fornearly 55 percent of the HIV population while West Bengal, Gujarat, Bihar andUttar Pradesh collectively account for 22 percent of the HIV/AIDS population inIndia. The main reasons for the spread of this deadly disease in India havebeen recognized as unprotected sex between sex workers and their clients, usageof infested injecting tool for drug infusion. Thus, sex workers form a majorsection of the HIV positive women in India. This study intends to comprehendthe status of the women HIV patients in India, understand their presentsituation and what atrocities they have to face within the family and societydue to their HIV status.